2019
DOI: 10.3390/nu11081845
|View full text |Cite
|
Sign up to set email alerts
|

Hormones in Breast Milk and Effect on Infants’ Growth: A Systematic Review

Abstract: Breast milk is characterized by a dynamic and complex composition which includes hormones and other bioactive components that could influence infant growth, development, and optimize health. Among the several beneficial effects associated with prolonged breastfeeding, a 13% decrease in the risk of overweight and obesity has been reported. Recent research has focused on breast milk hormones contributing to the appetite and energy balance regulation and adiposity. Accordingly, we conducted a literature systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 37 publications
0
50
0
4
Order By: Relevance
“…Neither leptin nor adiponectin displayed significant associations with infant growth outcomes in the long term, despite some studies suggesting that these compounds may also have a role in infant development and growth (28,59,60). Overall, the existing literature in this context is conflicting [see (37) for review] and disparities in the findings are, in part, likely due to different approaches as regards sample collection and storage, laboratory approaches used and statistical analysis of the data, as infant growth is influenced by a complex array of factors. While some of these, including basic characteristics, that can be identified and controlled for, other factors, including potential synergism/antagonism between our hormones of interest and other bioactive factors in HM (37), are difficult to control for.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither leptin nor adiponectin displayed significant associations with infant growth outcomes in the long term, despite some studies suggesting that these compounds may also have a role in infant development and growth (28,59,60). Overall, the existing literature in this context is conflicting [see (37) for review] and disparities in the findings are, in part, likely due to different approaches as regards sample collection and storage, laboratory approaches used and statistical analysis of the data, as infant growth is influenced by a complex array of factors. While some of these, including basic characteristics, that can be identified and controlled for, other factors, including potential synergism/antagonism between our hormones of interest and other bioactive factors in HM (37), are difficult to control for.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the existing literature in this context is conflicting [see (37) for review] and disparities in the findings are, in part, likely due to different approaches as regards sample collection and storage, laboratory approaches used and statistical analysis of the data, as infant growth is influenced by a complex array of factors. While some of these, including basic characteristics, that can be identified and controlled for, other factors, including potential synergism/antagonism between our hormones of interest and other bioactive factors in HM (37), are difficult to control for. The lack of associations in the present cohort between HM adipokine concentrations and infant BMI and weight does not preclude associations with infant body composition per se, as leptin in particular has been linked to eating behavior and fat mass (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assessed the associations between iodine and growth-and obesity-related hormones in breast milk and T A B L E 1 Basic characteristics of mothers and infants, n = 94 Although it is difficult to investigate how breastfeeding influences and regulates both short-and possibly long-term growth, there are some studies indicating that breast milk composition might play an important role in determining infant growth (Lind, Larnkjaer, Molgaard, & Michaelsen, 2018). Of all the bioactive compounds identified in breast milk, AD and LP are the most common hormones studied with regard to growth (Fields et al, 2016;Mazzocchi et al, 2019). It has been shown that AD might have insulin-sensitizing effects, and LP might induce satiety in the infants.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the crucial role of neuronic acid in white matter development, its content in human milk through the first month of lactation has been quantified and compared with that of formula milk from three fat sources [19]. Human milk's hormonal content, which seems to be involved in infants' metabolic pathways, including appetite and energy balance, has been also examined in light of the reduced risk of developing overweight and metabolic syndrome in human milk-fed infants [20,21].…”
mentioning
confidence: 99%